Disparities in Marriage Dispensation Due to Pregnancy: Analysis of Vage Women Norm and Maṣlaḥah Mursalah - Jumrotunisak Jumrotunisak; Khairil Anwar; Mowafg Abrahem Masuwd (MASI Mandiri Edukasi, 2026)
This study examines the disparity in marriage dispensation decisions in cases of pregnancy outside marriage at the Pangkalan Bun Religious Court. The research examines the ambiguity of the phrase “very urgent reasons” in Indonesian marriage law, which affords broad judicial discretion and may lead to inconsistent decisions. The objective of this study is to analyze how judges interpret and apply this provision in deciding marriage dispensation cases involving pregnancy. This research employs a qualitative normative approach by analyzing 32 court decisions issued by the Pangkalan Bun Religious Court, complemented by interviews with judges. The data were analyzed using thematic coding to identify recurring patterns in judicial reasoning. The findings reveal two dominant orientations in judicial considerations. The first orientation emphasizes protecting the unborn child's lineage and legal status, which often leads to approval of dispensation requests. The second orientation focuses on long-term child protection, considering factors such as psychological maturity, economic readiness, and the sustainability of future family life, resulting in the rejection of some petitions despite pregnancy. The disparity in decisions reflects the open-ended nature of the legal norm and demonstrates the dynamics of judicial ijtihad in balancing legal certainty and public interest. This study recommends the development of clearer interpretative parameters to promote consistency while ensuring stronger child protection in marriage dispensation practices.